1997
DOI: 10.4141/p96-013
|View full text |Cite
|
Sign up to set email alerts
|

Current state of cold hardiness research on fruit crops

Abstract: This article gives an overview of the current state of cold hardiness research in fruit crops by reviewing the recently published studies on cold hardiness of both tree fruit and berry crops. Topics discussed include cold hardiness of fruit species, cultivars and different plant organs, biophysical and biochemical aspects of hardiness, evaluation of hardiness, as well as endogenous, cultural and environmental factors affecting cold hardiness in these species. Lack of cold hardiness is a major limiting factor f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 155 publications
1
22
0
Order By: Relevance
“…A range of different methods can be used to evaluate injury after artificial freezing in controlled conditions [5]. The most frequently used methods for freezing injury assessment are visual rating of injury and electrical conductivity (EC) of diffused electrolytes [6].…”
Section: Introductionmentioning
confidence: 99%
“…A range of different methods can be used to evaluate injury after artificial freezing in controlled conditions [5]. The most frequently used methods for freezing injury assessment are visual rating of injury and electrical conductivity (EC) of diffused electrolytes [6].…”
Section: Introductionmentioning
confidence: 99%
“…Davarynejad et al (2009) indicated that the most sensitive organ of walnut genotypes was female buds, followed by male buds, vegetative buds, annual shoots and finally biannual shoots. Palonen and Buszard (1997) indicated that flower bud hardiness of apples did not seem related to hardiness of woody tissue. In P. davidiana the shoot was hard, however, the reproductive bud was sensitive (Ackerman 1969).…”
Section: Visual Observationsmentioning
confidence: 99%
“…During an environmental stress like low temperatures, the osmotic regulation takes on a resistance role to cold by cell accumulation of (Palonen and Buszard 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Freezing tolerance is an active trait, responsive to environmental fluctuations and it is genotype dependent for the timing of acclimation and dormancy, genetic potential for mid-winter freezing tolerance, rate of deacclimation, ability to reacclimate and timing of budbreak (Stushnoff, 1972). Therefore, winter survival is a multi-trait phenomenon that is impacted by photoperiod, temperature and water and nutritional status; all of which can interact differentially with genotype and tissue developmental stages (Fennell, 2004;Gusta and Wisniewski, 2012;Palonen and Buszard, 1997;Stushnoff 1972). Progress in selecting sustainable cultivars requires identifying critical phenotypes and susceptible tissues as well as critical environmental events (early fall freeze, mid-winter ultimate low temperature, deacclimation events).…”
Section: Winter Survival In Woody Temperate Fruit Cropsmentioning
confidence: 99%